Pedoman Penulisan JAB + back cover - JAB Cebis UNPAR (Jurnal Administrasi Bisnis, 2009)
CeBiS is the Center for Business Studies, was established by Department ofBusiness Administration, Faculty of Social and Political Science, Catholic Universityof Parahyangan.The Mission of the center is to contribute actively in business knowledgedevelopment through empirical research and theoretical studies. The main areaof research and studies are focused either in functional or sectoral businesses.Functional businesses include knowledge in financial and accountancy, human resources,organizational behavior, marketing, operational, leadership, communication,and entrepreneur. Meanwhile, sectoral businesses include in area services, retail,international business, and other business sector in general.The Center organizes some activities such as regularly discussion of the invitedspeaker, seminar and national conference in business topics, training and consultation.The Center also conducts research in theoretical or empirical in businessissues. And the Center published a biannual national scientific journal in BusinessAdministration, which is ”Jurnal Administrasi Bisnis”.The Center also maintain business databases, which hold some data in widerange of business sector, functional area, and particular aspect of business. Thedatabases also include technical report and working paper.